Pesantren’s Dormitory Design Parameters Based on Student’s Preference and Adaptation (EMARA: Indonesian Journal of Architecture, 2018)
Currently the development of pesantren in Indonesia is very rapid, while there is still no concept that is used as a reference in designing of the dormitory building. There are several standards or references used in dormitories but currently only found for campus dormitories. In addition, there are some problems in pesantren dormitory such as infrastructure that is less supportive and very high occupancy density, therefore students make adaptations. This study aims to formulate the parameters used in designing pesantren based on preferences and adaptation. Preference is included because there is relationship between preference and adaptation. The method used is qualitative by comparing from some literatures. The results consist of thread of thought, determining of pesantren and variable, indicator used. There are five thread that used to formulated design concept, among others existing, typology, preference, adaptation and proposal design. Variable and indicators of activity, facility and environmental scope can be assessed on student preference and adaptation in any contexts and type of pesantren. Further, the upcoming result of parameter can be set as the underlying consideration for the designing of pesantren dormitory.